A Bifan Motif Shaped by ArsR1, ArsR2, and Their Cognate Promoters Frames Arsenic Tolerance of Pseudomonas putida - Durante-Rodríguez, Gonzalo; Páez-Espino, David; de Lorenzo, Víctor (Frontiers in Microbiology, 2021)
operons encoding an As (III)-responsive repressor (ArsR), an As (V)-reductase (ArsC) and an As(III)-export pump (ArsB), often accompanied by other complementary genes. Enigmatically, the genomes of many environmental bacteria typically contain two or more copies of this basic genetic device arsRBC. To shed some light on the logic of such apparently unnecessary duplication(s) we have inspected the regulation—together and by separate—of the two ars clusters borne by soil bacterium Pseudomonas putida strain KT2440, in particular the cross talk between the two repressors ArsR1/ArsR2 and the respective promoters. DNase I footprint and gel retardation analyses of Pars1 and Pars2 with their matching regulators revealed non-identical binding sequences and interaction patterns for each of the systems. However, in vitro transcription experiments exposed that the repressors could down-regulate each other's promoters, albeit within a different set of parameters. The regulatory frame that emerges from these data corresponds to a particular type of bifan motif where all key interactions have a negative sign. The distinct regulatory architecture that stems from coexistence of various ArsR variants in the same cells could enter an adaptive advantage that favours the maintenance of the two proteins as separate repressors.